Assessment of Foetal Malnutrition Using CAN Score and its Comparison With Various Anthropometric Parameters and Proportionality Indices - Kapoor, Anju; Awasthi, Sukarn; Yadav, Ankit; Tiwari, Shraddha (Journal of Nepal Paediatric Society, 2021)
Introduction: Nutritional status at birth is assessed by using various anthropometric parameters and proportionality indices. Present study aims to assess the utility of CAN score in identifying fetal malnutrition (FM) which would have been missed by using anthropometry alone. We also aim at re-evaluating the cut-off value of CAN score for our population. Methods: Nutritional status of 411 neonates was assessed using anthropometric parameters, proportionality indices and CAN score. Effectiveness of each parameter in detecting FM was assessed and compared with CAN score cutoff < 25 as well as new found cut-off < 27 using appropriate statistical tools. Result: Mean (SD) of all anthropometric parameters were significantly less in FM group (p < 0.001). CAN score identified FM in 18.5% (76 / 411) babies whereas weight for GA identified 8.8% (36 / 411) babies as SGA and 91.2% as AGA (375 / 411); 12.3% (46 / 375) babies identified as AGA, were found to be malnourished by CAN score. Similar trend is seen with other parameters too. ROC curves show that AUC for birth weight, mid arm circumference, body mass index, Ponderal index, length and MAC / HC for determining FM was 0.891, 0.855, 0.837, 0.761, 0.749 and 0.714 in decreasing order. Birth weight with cut-off 2300 grams in a term newborn has maximum AUC making it the best marker for predicting FM. Present study identifies more FM by using modified CAN score cut off < 27 instead of < 25, 32.11% (132 / 411) and 18.5% (76 / 411) respectively. Conclusion: CAN score is a simple method to assess FM which does not require any sophisticated equipment or time-consuming calculations.